2011
DOI: 10.1039/c1cp20255c
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic ionic liquid stabilizing palladium nanoparticles for highly efficient catalytic hydrogenation

Abstract: The highly water-soluble palladium nanoparticles (NPs) were synthesized by using the amphiphilic poly(ethylene glycol)-functionalized dicationic imidazolium-based ionic liquid (C(12)Im-PEG IL) as a stabilizing agent. The aqueous dispersed palladium NPs in the range of 1.9 ± 0.3 nm were observed by transmission electron microscopy (TEM). The physicochemical properties of C(12)Im-PEG IL in aqueous phase have been characterized by electrical conductivity, surface tension and dynamic light scattering (DLS) measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Diimidazolium‐based DOSs have also been used as agents for stabilizing palladium nanoparticles. Hou et al reported data on the synthesis of highly water‐soluble palladium nanoparticles through the use of a dicationic PEG‐based IL 28 with chloride anions (Scheme ) 53…”
Section: Applicationsmentioning
confidence: 99%
“…Diimidazolium‐based DOSs have also been used as agents for stabilizing palladium nanoparticles. Hou et al reported data on the synthesis of highly water‐soluble palladium nanoparticles through the use of a dicationic PEG‐based IL 28 with chloride anions (Scheme ) 53…”
Section: Applicationsmentioning
confidence: 99%
“…23 In some other cases, the reported catalytic ability is a result of the formation of an organometallic complex. 24,25 Here, we describe the structure-property relationships and thermal behaviour of a series of multi-positive imidazolium ionic liquids paired with multi-negative anions with respect to properties and applications. [26][27][28][29][30] In particular, we thought it could be interesting to study new dicationic ionic liquids functionalised with a basic moiety.…”
Section: Introductionmentioning
confidence: 99%
“…For example Zhu et al reported the formation of well-dispersed palladium colloids in amphiphilic imidazolium-based ionic liquids that acted simultaneously as stabilizers for the nanoparticles and as surfactants generating an emulsion for the hydrophobic substrates. 46 Palladium nanoparticles were prepared in aqueous solution via hydrogenation, and are formed independent of the concentration range of the ionic liquid. When assessing the impact of ionic liquid concentration on the catalytic activity, the authors observed a constant increase in turn-over frequency (TOF) that continued distinctly above the CMC of the respective ionic liquid, and only decreases slowly at very high concentrations.…”
Section: Resultsmentioning
confidence: 99%